James Whatman II at the Old Bailey. (10th March 2018) - Day, Geoffrey; Junqua, Amélie
Abstract: This note describes how James Whatman II, the pre-eminent British paper-maker, was the expert witness at the Old Bailey on 26 July 1783 when William Wynne Ryland was indicted for 'having in his custody and possession, a certain bill of exchange, purporting to bear date at Fort St George in the East Indies' for £200. There were seven further counts in the indictment, specifying intention to defraud and naming the various parties concerned, the most important being the East India Company. At this trial Whatman provided key details about the practices in his mill and his business dealings with London stationers.